1991
DOI: 10.1016/0020-7292(91)90227-v
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum colposcopy of the cervix: injury and healing

Abstract: Colposcopic examination was done in 189 successive parturients within 6-48 h of delivery for evidence of type, site, and extent of cervical trauma and its relation to various obstetric factors. There was trauma in 66% of cases, as erosion in 79%, as laceration in 56%, as bruising in 30%, and as yellow areas in 17%. In about two-thirds of cases, the diameter of cervical erosion, or the length of laceration did not exceed 5 mm and 81% of lacerations were of first degree. Cervical injury was significantly more fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…β actin was used as the normalizer. n=5 of this phase of CR is potentially vital as it may improve our understanding of obstetrical complications that may be associated with this period, such as cervicitis, ectropion, hemorrhage, repeated miscarriages or abortions and, possibly, preterm labor and malignancies (Fahmy et al 1991). The present study is the first comprehensive postpartum study and uses a variety of techniques to examine the morphological and molecular changes in the mouse cervix during the first 48 h of postpartum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…β actin was used as the normalizer. n=5 of this phase of CR is potentially vital as it may improve our understanding of obstetrical complications that may be associated with this period, such as cervicitis, ectropion, hemorrhage, repeated miscarriages or abortions and, possibly, preterm labor and malignancies (Fahmy et al 1991). The present study is the first comprehensive postpartum study and uses a variety of techniques to examine the morphological and molecular changes in the mouse cervix during the first 48 h of postpartum.…”
Section: Discussionmentioning
confidence: 99%
“…The cervix undergoes marked changes during pregnancy, as well as significant trauma during normal vaginal delivery of the baby at birth (parturition) and immediately postpartum (after birth) (Timmons et al 2010). As such, a timely and complete postpartum tissue repair is necessary to prevent obstetrical complications, such as cervicitis, ectropion, hemorrhage, repeated miscarriages or abortions and, possibly, preterm labor and malignancies (Fahmy et al 1991). For instance, during pregnancy, the cervix has to contain and withstand an ever increasing gravitational force exerted by the rapidly growing fetus in order to ensure that it (the fetus) is held in utero (Timmons et al 2010), whereas at parturition, under the intense force of the contracting uterus, the ripened cervical tissue is forced to expand and dilate to ultimately allow passage of the fetus through the birth canal (Mahendroo 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Lacerations that required a surgical repair to stop bleeding were considered to be clinically significant. However, in one study, stable, hemostatic cervical injuries were identified by colposcopy 6 to 48 hours after vaginal birth in 66% of cases, indicating that CLs may be occurring at higher rates 6 . The lateral sides of the cervix (“3 and 9 o'clock”) are the most common locations for a laceration, but any location on this circular tissue is subject to injury 7 .…”
Section: Cervical Lacerationsmentioning
confidence: 99%
“…However, in one study, stable, hemostatic cervical injuries were identified by colposcopy 6 to 48 hours after vaginal birth in 66% of cases, indicating that CLs may be occurring at higher rates. 6 The lateral sides of the cervix ("3 and 9 o' clock") are the most common locations for a laceration, but any location on this circular tissue is subject to injury. 7 Defects may be small and hemostatic, but others may result in extensive bleeding, as demonstrated in this case.…”
Section: Incidencementioning
confidence: 99%
See 1 more Smart Citation